Credit Card Holders and Users as a Means of Payment in Legitimate Commercial Transactions - Tjandraningsih, Dewi (The International Journal of Education Management and Sociology, 2024)
This study aims to examine the legal aspects of credit card usage as a payment tool in commercial transactions, focusing on the mechanism of credit card use in buying and selling transactions, as well as legal protection for the parties involved. The research employs a normative juridical approach, relying on secondary data as the primary research material. Data was obtained from documents provided by Bank Danamon and BCA in Tangerang and analyzed using a normative qualitative method. Credit cards, issued by banks in Indonesia, are a form of credit facility provided by the issuing bank to users, enabling them to make purchases at designated locations. The findings reveal that, from a legal perspective, the use of credit cards involves incidental agreements that arise at the moment of a transaction, whether it is a purchase or a service. While the mechanisms for approval differ between issuing banks, the requirements and procedures are relatively similar. Legal protection for the parties involved in credit card transactions occurs during the signing of the credit card agreement between the issuer and the cardholder. However, there is no explicit legal framework governing this matter. Common challenges include fraud, forgery, and theft. To mitigate these risks, it is recommended to store credit cards securely, ensure the inclusion of signatures and photos on the front panel of the card, and prohibit card transfer to third parties. In the event of card loss, the cardholder must immediately contact the issuing bank.